2017
DOI: 10.3892/ol.2017.6321
|View full text |Cite
|
Sign up to set email alerts
|

Curcumin induces apoptotic cell death in human pancreatic cancer cells via the miR-340/XIAP signaling pathway

Abstract: Abstract. The natural compound curcumin has previously been reported to inhibit pancreatic cancer cell growth. However, the underlying molecular mechanisms underlying this effect remain unclear. Results from the present study demonstrate that the miR-340/X-linked inhibitor of apoptosis (XIAP) signaling pathway mediates curcumin-induced pancreatic cancer cell apoptosis. miR-340 was identified to be significantly upregulated following curcumin treatment. In addition, treatment with curcumin or miR-340 induced pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 37 publications
3
16
0
1
Order By: Relevance
“…Previous studies showed that the anti-tumor activities of curcumin are mainly due to the inhibition of proliferation, migration and invasion, as well as due to the induction of apoptosis [ 11 , 15 , 22 ]. This study revealed that curcumin significantly reduced the viability and colony formation of both SO-Rb50 and Y79 cells, and the IC50 value of curcumin in these two Rb cell lines is about 35 μM.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies showed that the anti-tumor activities of curcumin are mainly due to the inhibition of proliferation, migration and invasion, as well as due to the induction of apoptosis [ 11 , 15 , 22 ]. This study revealed that curcumin significantly reduced the viability and colony formation of both SO-Rb50 and Y79 cells, and the IC50 value of curcumin in these two Rb cell lines is about 35 μM.…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that curcumin exerted anti-tumor activities via modulation of various miRNAs, including miR-21 [ 14 ], miR-340 [ 15 ] and miR-98 [ 16 ]. Curcumin could alter the expression of many miRNAs in Y79 cells [ 41 ], which may contribute to its anti-tumor properties in Rb.…”
Section: Discussionmentioning
confidence: 99%
“…miRNAs are a class of short, endogenous, non‐coding RNAs that play important roles in gene regulation by binding to, and repressing the expression of target mRNAs in a sequence‐dependent method. In particular, a number of reports have identified miR‐340 as a tumor suppressor in HCC as well as several other cancers including ovarian cancer, breast cancer, colon cancer, glioblastoma, and pancreatic cancer . Consistent with these data, in a previous study, we found that miR‐340 expression was significantly downregulated in HCC tissues compared with normal liver tissues.…”
Section: Introductionsupporting
confidence: 91%
“…In particular, a number of reports have identified miR-340 as a tumor suppressor in HCC 9,10 as well as several other cancers including ovarian cancer, 11 breast cancer, 12 colon cancer, 13 glioblastoma, 14 and pancreatic cancer. 15 Consistent with these data, in a previous study, we found that miR-340 expression was significantly downregulated in HCC tissues compared with normal liver tissues. Furthermore, we showed that HBV could downregulate miR-340 in hepatoma cells, which facilitates their migration.…”
Section: Introductionsupporting
confidence: 89%
“…It consequently causes an induction of FOXO1 (forkhead box O1). A more recent study proposed that apoptosis induced by Cur is the result of activation of miR-340 and the downregulation of its target anti-protein, XIAP (X linked inhibitor of apoptosis protein) (Yang et al, 2017). The above studies demonstrate Cur's anticancer properties describe the mechanism and provide preliminary evidence for its potential use to sensitize PC cells to cytotoxic therapies.…”
Section: Curcumin and Its Anti-cancer Propertiesmentioning
confidence: 80%